1985
DOI: 10.1002/mus.880080607
|View full text |Cite
|
Sign up to set email alerts
|

Endoneurial injection of antisera to myelin antigens

Abstract: When antisera to purified myelin antigens were injected into rat sciatic nerves, some produced significant demyelination, whereas others merely induced an inflammatory infiltrate. Extensive demyelination was produced by antisera to galactocerebroside and the peripheral nerve glycoprotein P0. Demyelination resulting from injections of antisera to ganglioside GM1, P2, myelin basic protein, sulfatide, and glucocerebroside did not exceed that produced by normal rabbit serum. Addition of guinea pig complement had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…to avoid this issue. The inflammation and demyelination found in the control rats injected with PBS was not unexpected, as previous studies have shown 16 . It is well known that nervous tissue trauma provokes or enhances myelin antigen autoreactive T‐ and B‐cell responses 17 and may provoke immunopathological events 18 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…to avoid this issue. The inflammation and demyelination found in the control rats injected with PBS was not unexpected, as previous studies have shown 16 . It is well known that nervous tissue trauma provokes or enhances myelin antigen autoreactive T‐ and B‐cell responses 17 and may provoke immunopathological events 18 .…”
Section: Discussionsupporting
confidence: 53%
“…Therefore we followed many of the recommendations of Dyck et al 14 . and Hugues et al 16 . to avoid this issue.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore cannot exclude the possibility that they are the consequence rather than the cause of the disease, a criticism that could be levelled at the evidence for many auto-immune diseases. The experimental observation that experimental and human anti-P0 antibodies induce demyelination following intraneural injection lends support to the hypothesis that they play a part in pathogenesis (Hughes et al, 1985;Yan et al, 2001).…”
Section: Characteristics Of Patients With Antibodiesmentioning
confidence: 68%
“…Administration of antibodies alone does not induce disease, probably because they do not reach the endoneurium. Intraneural injection of antibodies directed against myelin antigens, especially those such as galactocerebroside and P0 which are abundantly expressed at the myelin–Schwann cell surface, induces demyelination ( Hughes et al, 1985 ) . The models most studied have been acute, with disease developing after about 10 days, reaching a nadir after about 15 days and recovering substantially by 28 days.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…With the possible exception of P0, there is no convincing evidence of antibodies to myelin proteins being formed in CIDP. By contrast, antibodies to proteins such as P0 which are expressed at the myelin–Schwann cell surface do cause demyelination upon intraneural injection ( Hughes et al, 1985 ) and remain possible agents of demyelination in CIDP. The detection of antibodies to P0 and other myelin protein antigens is likely to be critically dependent on the conformation of the antigen which may only be realized on the intact protein in its usual membrane environment.…”
Section: Antibodiesmentioning
confidence: 99%